Occurrence of virulence-associated genes in Arcobacter butzleri and Arcobacter cryaerophilus isolates from foodstuff, water, and clinical samples within the Czech Republic - Šilha, David; Vacková, Barbora; Šilhová, Lucie (My University, 2019)
Bacteria of the Arcobacter (A.) genus, originating mainly from food and water, are dreaded germs for humans as well as animals. However, the virulence of these bacteria has not been fully elucidated yet. This study looked at the occurrence of eight selected virulence factors (ciaB, cj1349, pldA, irgA, hecA, tlyA, mviN, hecB) in a total of 80 strains of A. butzleri and 22 strains of A. cryaerophilus. The strains included in this study were derived from samples of food and water, but there were also strains from patients suffering from arcobacteriosis. A polymerase chain reaction using specific primers was used to detect these virulence–associated genes. The presence of the observed genes was observed in the strains of A. butzleri (98.8% ciaB, 95.0% cj1349, 98.8% pldA, 22.5% irgA, 31.3% hecA, 95.0% tlyA, 97.5% mviN, 38.8% hecB), and A. cryaerophilus (95.5% ciaB, 0.0% cj1349, 9.1% pldA, 0.0% irgA, 0.0% hecA, 31.8% tlyA, 90.9% mviN, 0.0% hecB), but to a varying extent. Among the tested strains, there were 13 strains (12.7%) of A. butzleri, in which the presence of all 8 virulence–associated genes was recorded in the genome. In contrast, in one A. cryaerophilus strain, none of the observed genes were detected. The presence of ciaB and mviN genes was significantly more frequent in A. cryaerophilus isolates than in other genes (P ≤ 0.05). In general, more virulent genes have been detected in A. butzleri strains (the most common gene combination of ciaB, cj1349, pldA, tlyA, mviN detected in 39 strains) compared to A. cryaerophilus. In 50.0% of A. butzleri strains derived from cases of human enteritis, all 8 virulent genes were significantly more frequently detected (P ≤ 0.05).
Výskyt genů faktorů virulence u izolátů Arcobacter butzleri a Arcobacter cryaerophilus izolovaných z potravin, vody a klinických vzorků v rámci České republiky
Keywords: Arcobacter butzleri; Arcobacter cryaerophilus; virulence factor; PCR; Arcobacter butzleri; Arcobacter cryaerophilus; virulenční faktory; PCR